Модели материалов арматуры и бетона для теплотехнических и прочностных расчетов на примере российского стандарта - Kamlyuk Андрей; Polevoda Иван; Shirko Алексей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The parametric models of reinforced concrete slabs, beams and columns were developed. The nonlinear material models of concrete and reinforcing steel, which include elastic-plastic, temperature-related stress-strain relationship, as well as cracking in the concrete, were found. The results will form the basis for program evaluation of fire resistance of structural elements.